Expression of IL-25, IL-33, and Thymic Stromal Lymphopoietin in Nasal Polyp Gland Duct Epithelium in Patients With Chronic Rhinosinusitis. Issue 4 (July 2019) - Nagata, Yoshiyuki; Maruoka, Shuichiro; Gon, Yasuhiro; Mizumura, Kenji; Kishi, Hiroyuki; Nomura, Yasuyuki; Hikichi, Mari; Hashimoto, Shu; Oshima, Takeshi
Background: Nasal polyps accompany eosinophilic chronic rhinosinusitis (ECRS). Cytokines, including interleukin (IL)-25, IL-33, and thymic stromal lymphopoietin (TSLP) expressed in nasal mucosa have been implicated in polyp pathogenesis. We investigated the role of nasal polyp epithelium cytokine expression in eosinophilic infiltration in ECRS. Methods: Tissues were collected from 39 patients undergoing nasal surgery. Cases were divided into 3 groups: control (CTR), non-ECRS (nECRS), and ECRS and were evaluated for IL-25, IL-33, and TSLP expression. Results: Abundant eosinophilia was observed underneath the nasal mucosa and around the nasal ducts in polyps in ECRS and correlated positively with IL-33 protein expression. Conclusion: Cytokine expression in nasal duct cells and eosinophilic infiltration around duct cells similar to those in the nasal mucosa occurred in the nasal epithelium of polyps, suggesting its role in inducing eosinophilic inflammation.